2015
DOI: 10.1371/journal.pone.0142640
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Di-D-Fructofuranose 1,2’:2,3’ Dianhydride (DFA III) Hydrolysis Enzyme from Arthrobacter aurescens SK8.001

Abstract: Previously, a di-D-fructofuranose 1,2’:2,3’ dianhydride (DFA III)-producing strain, Arthrobacter aurescens SK8.001, was isolated from soil, and the gene cloning and characterization of the DFA III-forming enzyme was studied. In this study, a DFA III hydrolysis enzyme (DFA IIIase)-encoding gene was obtained from the same strain, and the DFA IIIase gene was cloned and expressed in Escherichia coli. The SDS-PAGE and gel filtration results indicated that the purified enzyme was a homotrimer holoenzyme of 145 kDa c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…H65-7 has no activity toward inulin . Other DFA-IIIases’ ,, activity toward inulin was not studied. However, we found that AcDFA-IIIase was also able to decompose inulin under the same conditions as those used for hydrolyzing DFA-III.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…H65-7 has no activity toward inulin . Other DFA-IIIases’ ,, activity toward inulin was not studied. However, we found that AcDFA-IIIase was also able to decompose inulin under the same conditions as those used for hydrolyzing DFA-III.…”
Section: Resultsmentioning
confidence: 99%
“…After centrifugation (18 000 g , 4 °C, 20 min) and filtration using a 0.22 μm filter, the filtrate was analyzed by the Sugar-Pak I column (Waters, Milford, MA) with an Agilent 1200 HPLC system (Agilent Technologies, Santa Clara, CA) and a refractive index detector. The standard marker of inulobiose was synthesized by our previously obtained DFA-IIIase . The amount of AcDFA-IIIase or its mutant that produces 1 μmol inulobiose per minute at pH 6.5 and 55 °C was defined as one unit of activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The putative inulin utilization region consists of three co-oriented genes. It comprises a gene encoding an enzyme similar to an inulinfructotransferase (65.71% similarity) previously described in Arthrobacter (Yu et al, 2015).…”
Section: Genomic Features Associated With Metabolic Variationmentioning
confidence: 99%
“…Their unique cyclic structure confers on DFAs much higher enzymatic and chemical stability as compared with classical fructosyl derivatives such as sucrose. , The growing interest in the prebiotic properties of DFAs has led to the search for new methodologies allowing the preparation of single isomers or DFA-enriched products. A method based on the enzymatic catalytic degradation of fructans was one of the first studied. More recently, the enzymatic synthesis of a DFA diastereomer from sucrose, namely, α- d -fructofuranose β- d -fructofuranose 1,2′:2,3′-dianhydride, by coupling a sucrose fructosyltransferase and an inulin fructotransferase, has also been reported . Major drawbacks of these syntheses are the low thermal stability, the substrate dependence of enzymes, and the high cost of these processes.…”
Section: Introductionmentioning
confidence: 99%